The dividing wall: Ephesians and the integrity of the Corpus Paulinum - Wright, Martin (Library of New Testament studies, 2021)
"This volume critiques preoccupation with the authorship of the Pauline letters, and argues for more integrative and interpretive readings of the Pauline Corpus"--